Pengaruh Budaya Organisasi, Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan - Ai Elis Karlinda; Muhammad Ridwan; Omia Crefioza; Neni Sri Wahyuni Nengsi (CV. ITTC INDONESIA, 2026)
Employee performance is a critical factor in determining an organization's ability to achieve its strategic objectives. Organizational culture, transformational leadership, and work motivation are widely recognized as important factors influencing employee performance. However, previous studies have produced inconsistent findings, highlighting the need for further investigation. This study aims to examine the effects of organizational culture, transformational leadership, and work motivation on employee performance at PT Cipta Kridatama Site KIM, Jambi. This research employed a quantitative approach with a causal research design. The population consisted of all employees of the Human Capital Affairs (HCA) and Mining Academy (MA) divisions at PT Cipta Kridatama Site KIM, Jambi, totaling 70 employees. A saturated sampling technique was applied, whereby the entire population was selected as the research sample. Primary data were collected through a structured questionnaire, while data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The findings indicate that organizational culture does not have a positive and significant effect on employee performance. In contrast, transformational leadership and work motivation have positive and significant effects on employee performance. The findings imply that improving employee performance at PT Cipta Kridatama Site KIM should primarily focus on strengthening transformational leadership practices and enhancing employees' work motivation rather than relying solely on organizational culture.